2018
DOI: 10.1177/1471301218791906
|View full text |Cite
|
Sign up to set email alerts
|

What would most help improve the quality of life of older family carers of people with dementia? A qualitative study of carers’ views

Abstract: Older family carers of people with dementia provide a substantial amount of care for people with dementia in the UK. Caregiving can be stressful and burdensome for these individuals, who are also experiencing psychological and physical changes resulting from their own ageing process. However, little is known about what impacts their quality of life, how this can be improved and what we should prioritise. This brief report asks one simple question to older family carers of people living with dementia - "What wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
0
10
0
6
Order By: Relevance
“…Increasing caring responsibilities and time commitments can lead to family carers experiencing a 'shrinking world', in which maintaining access to social and physical realms beyond the home becomes difficult (Davies et al, 2019;Ward et al, 2018). Decreased financial and economic well-being is another common consequence associated with caring for a person with dementia (Oliveira et al, 2020). Out-of-pocket care-related expenses account for 11% of annual household income for families of dependent people without dementia in the last five years of their life.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing caring responsibilities and time commitments can lead to family carers experiencing a 'shrinking world', in which maintaining access to social and physical realms beyond the home becomes difficult (Davies et al, 2019;Ward et al, 2018). Decreased financial and economic well-being is another common consequence associated with caring for a person with dementia (Oliveira et al, 2020). Out-of-pocket care-related expenses account for 11% of annual household income for families of dependent people without dementia in the last five years of their life.…”
Section: Introductionmentioning
confidence: 99%
“…De forma geral, a presente revisão evidenciou a escassez de publicações primárias relacionada à qualidade de vida do cuidador familiar idoso frente ao processo de cuidar de um idoso doente. DQol-OC -Dementia Quality of Life Scale for Older Family Carers, utilizado para avaliação da QV de cuidadores familiares idosos de pessoas com demência (Oliveira et al, 2017a(Oliveira et al, , 2017b(Oliveira et al, , 2018; Q-LES-Q-SF -Quality of Life Enjoyment and Satisfaction Questionnaire Short Form, avaliação das percepções de prazer e de satisfação (Bormann et al, 2009), e SF-12 -Short Form Health Survey, que considera 12 itens com duas dimensões: saúde física (PCS12) e saúde mental (MCS12) (Ekwall et al, 2004;Fagerström et al, 2020). O instrumento DQol-OC, a partir das duas questões abertas, possibilitou aos cuidadores a oportunidade de expressar os aspectos importantes e não abordados no questionário e geralmente, estes não estão disponíveis na maioria das outras escalas de QV (Oliveira et al, 2017a), permitindo a manifestação de colocações subjetivas e dos conteúdos ocultos nas falas dos participantes.…”
Section: Características Dos Estudos Incluídosreferentes à Tabelaunclassified
“…Os estudos evidenciaram uma variedade de fenômenos de interesse e de temas adotados quanto ao termo cuidador, seja ele: familiar (Canam & Acorn, 1999;Díaz-Veiga & Trocóniz, 2005;Bormann et al, 2009;Oliveira et al, 2017aOliveira et al, , 2017b, idoso (Rosas & Neri, 2019), de idoso (Oliveira et al, 2018), familiar idoso (Oliveira et al, 2017a(Oliveira et al, , 2017b(Oliveira et al, , 2018Fagerström et al, 2020) e informal (Ekwall et al, 2004;Flesch et al, 2019).…”
Section: Aspectos Dos Cuidadosunclassified
See 1 more Smart Citation
“…Recent studies (Daley et al, 2019; Frias et al, 2020; Hvidsten et al, 2020; Vun et al, 2020), systematic reviews (Farina et al, 2017; Oliveira et al, 2020; Pereira & Soares, 2015) and a meta-analysis (Contreras et al, 2020) have identified a number of factors that are associated with CGs’ QoL. These included CG’s variables , such as age, gender, physical and mental health problems, and burden, and the care-receiver’s characteristics , such as dementia symptoms as perceived by the CG.…”
Section: Introductionmentioning
confidence: 99%